Discourses of political participation among young Hungarians - Déri, András; Szabó, Andrea (POLARITIES, 2024)
Different macro- and meso-level theories of youth political participation focus on who participates in political action and why. However, little is known about how young people interpret these forms of participation and whether their actual participation is structured along these interpretations. Our study aims to show what discourses of political participation can be identified in Hungary and which are specific to young people. This question is particularly relevant in the pandemic that emerged after COVID-19, which confined young people's everyday interactions and political activism to the online space for almost two years. According to our ‘Asteroida Effects’ hypothesis, new forms of political participation may have emerged, which may have reinterpreted the previous dynamics between online and offline participation. After the third wave of the pandemic and during the fourth wave, we conducted six focus group discussions and eight semi-structured online interviews, which we analysed through discourse analysis. Our results show that, at least in part, young people have redefined political participation due to the asteroid impact and have included communication about it in the meaning field of political participation.